Pengembangan Bahan Ajar Membaca Permulaan Menggunakan Media Pop Up Book di Sekolah Dasar - Rina Permata Sari; Darnis Arief; Ahmad Sabandi; Farida Fachruddin (Universitas Negeri Padang, 2022)
The purpose of this research is to develop teaching materials for beginning reading using pop-up book media that are valid, practical, and effective. The research method used is a 4D model including Define, Design, Develop, and Disseminate. The teaching materials developed were analyzed by a team of experts. The research subjects were class II students. Practically, teaching materials are obtained through questionnaires for teacher and student responses. The effectiveness of teaching materials is seen from the control of student activities and learning outcomes. The results of the validation analysis are 86.84 very valid categories, the results of the practicality test are average and 91.64 are very practical categories and the effectiveness test results are obtained an average of 96 with very high categories Based on these results, it can be concluded that the initial reading teaching materials using pop up book media developed for Grade II Elementary School students are valid, practical, and effective.